1995
DOI: 10.1097/00005392-199505000-00076
|View full text |Cite
|
Sign up to set email alerts
|

High Flow Priapism Associated with Sickle Cell Disease

Abstract: Priapism associated with sickle cell disease is classically described as a low flow state. We report 2 cases of high flow priapism associated with sickle cell disease. High flow priapism has previously been reported almost exclusively in patients with traumatic rupture of the cavernous artery. Neither of our patients had historical or radiographic findings consistent with injury to the penile vasculature. One patient was treated unsuccessfully with intracorporeal injection of methylene blue and 1 underwent suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…7 Furthermore, although this is normally a low¯ow priapism, there have been several reports of high ow priapism in sickle patients for unknown reasons. 7,8 It has been hypothesized that high¯ow sickle priapism may result from a failure of the autonomic regulation. 9 Leukemia is the cause of less than 1% of all priapism.…”
Section: Hematologicathrombotic Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Furthermore, although this is normally a low¯ow priapism, there have been several reports of high ow priapism in sickle patients for unknown reasons. 7,8 It has been hypothesized that high¯ow sickle priapism may result from a failure of the autonomic regulation. 9 Leukemia is the cause of less than 1% of all priapism.…”
Section: Hematologicathrombotic Causesmentioning
confidence: 99%
“…39 In addition, Ramos et al reported the successful use of bilateral pudendal artery ligation for this condition. 8 The more de®nitive therapy for high¯ow priapism which is due to penile or perineal trauma or in certain idiopathic cases is either cavernosal artery ligation or embolization. 33 ± 35,38,56 ± 61 Embolization is usually recommended and surgery is reserved for failures.…”
Section: Therapy For High¯ow Priapismmentioning
confidence: 99%
“…Hematologic diseases are usually associated with a "low flow" priapism, but some associations have also been reported between "high flow" priapism and sickle cell anemia (6). Both type of priapism are also associated with Fabry disease (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Some have contended that the blood flow pattern resembles high-flow priapism based on radiographic study, in the absence of an arterialcavernosal fistula. [37][38][39][40] High-flow priapism has been clinically assessed in priapism related to medical diseases including Fabry's disease 41 and sickle cell disease. 37 Drug-induced priapism, which as suggested implies a medication-related phenomenon, represents another variant that has resulted from use of alpha-adrenergic antihypertensives, psychotropic agents, antidepressant medications, cocaine, and pharmacotherapeutic agents for erectile dysfunction.…”
Section: Abnormal Penile Blood Flowmentioning
confidence: 99%
“…[37][38][39][40] High-flow priapism has been clinically assessed in priapism related to medical diseases including Fabry's disease 41 and sickle cell disease. 37 Drug-induced priapism, which as suggested implies a medication-related phenomenon, represents another variant that has resulted from use of alpha-adrenergic antihypertensives, psychotropic agents, antidepressant medications, cocaine, and pharmacotherapeutic agents for erectile dysfunction. [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] The mechanism of action is contended to relate to peripheral and central signaling pathways stimulated by the offending drug that produce corporal smooth muscle relaxation.…”
Section: Abnormal Penile Blood Flowmentioning
confidence: 99%